Bioaccessibility of iron in pearl millet flour contaminated with different soil types. (15th February 2023) - Muleya, Molly; Young, Scott D.; Broadley, Martin R.; Joy, Edward J.M.; Chopera, Prosper; Bailey, Elizabeth H.
Highlights: Bioaccessibility of Fe in soil-contaminated pearl millet flour was determined. Soil properties determine Fe release under gastro-intestinal conditions. Soil contaminating pearl millet flour did not modify Fe bioaccessibility. Extrinsic soil Fe in crops is indicated by a strong positive Fe:V correlation. Abstract: A controlled in-vitro experiment was conducted to determine the bioaccessibility of extrinsic soil iron in pearl millet contaminated with typical Malawian soils. Pearl millet was contaminated with soils at ratios typically encountered in real life. Iron concentrations of soil-contaminated flour increased such that soil-derived iron contributed 56, 83 and 91% of the total iron when the proportions of soil were 0.1, 0.5 and 1% (soil: grain w/w), respectively. When soils were digested alone, the concentration of bioaccessible iron differed depending on the type of soil. However, the concentration of bioaccessible iron in soil-contaminated flours did not exceed that of uncontaminated flour and there was no effect of soil type. This suggests that knowledge of the proportion of extrinsic soil iron in soil-contaminated grains would be useful for iron bioavailability estimations. Vanadium is a reliable indicator of the presence of extrinsic soil iron in grains and has potential applications in this regard.